Type Passion, Family Life, Government Support: Explaining the Success of MSME Women Entrepreneurs - Ratnaningrum Ratnaningrum; Heni Susilowati; Titin Hargyatni; Dewi Widyaningsih; Ahmad Zaenuri (Research Synergy Foundation, 2023)
The Covid-19 pandemic is a hard time for entrepreneurs because economic activity will undoubtedly suffer. Women entrepreneurs, in particular, are more vulnerable to the pandemic's adverse effects on their businesses due to their dual role as entrepreneurs and housewives, which limits their movements more than men. This study investigates the impact of passion, family life, and government support on the success of women entrepreneurs. As a statistical analysis tool, the Partial Least Square Structural Equation Modeling method was employed. The findings show that passion and government support have a positive impact on the success of female entrepreneurs, whereas family life has no impact on it. The results are expected taken into account by the government so that the programs and systems put in place to support the success of women entrepreneurs can be maintained and improved.